2011
DOI: 10.1016/j.jad.2011.02.021
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and characteristics of complicated grief in older adults

Abstract: The prevalence of complicated grief in older adults in the general population was noteworthy. Several factors were predictive of complicated grief and it was demonstrated as a separate condition to anxiety and depression. These findings highlight the need for prevention, diagnosis and treatment options for older adults with complicated grief and for recognition of complicated grief as a distinct diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
160
4
23

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 232 publications
(203 citation statements)
references
References 28 publications
15
160
4
23
Order By: Relevance
“…The death of a child is a devastating event and is considered to be the most severe kind of loss (Kersting, Brahler, Glaesmer, & Wagner, 2011; Newson, Boelen, Hek, Hofman, & Tiemeier, 2011). Previous research has found that bereaved parents may experience mental health disorders such as depression, anxiety, insomnia, prolonged grief disorder (PGD), post-traumatic stress disorder (PTSD) and suicidal behaviours (Harper, O’Connor, & O’Carroll, 2014; Lannen, Wolfe, Prigerson, Onelov, & Kreicbergs, 2008; Rogers, Floyd, Seltzer, Greenberg, & Hong, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The death of a child is a devastating event and is considered to be the most severe kind of loss (Kersting, Brahler, Glaesmer, & Wagner, 2011; Newson, Boelen, Hek, Hofman, & Tiemeier, 2011). Previous research has found that bereaved parents may experience mental health disorders such as depression, anxiety, insomnia, prolonged grief disorder (PGD), post-traumatic stress disorder (PTSD) and suicidal behaviours (Harper, O’Connor, & O’Carroll, 2014; Lannen, Wolfe, Prigerson, Onelov, & Kreicbergs, 2008; Rogers, Floyd, Seltzer, Greenberg, & Hong, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Two further items (relating to seeing and hearing the deceased) were collapsed into one due to their similarity and to a pilot study indicating these symptoms were low in frequency and often overlapped ("I hear the voice of, or see, the person who died"). Several studies give further details on the interpretation of ICG (Boelen et al, 2010;Newson et al, 2011;Prigerson & Jacobs, 2001). We divided all interviewed participants into nongrievers (reference group), normal grievers, and complicated grievers.…”
Section: Assessment Of Complicated Griefmentioning
confidence: 99%
“…We divided all interviewed participants into nongrievers (reference group), normal grievers, and complicated grievers. Complicated grief symptoms were assessed as present among participants who scored equal or greater than 22 on the ICG score and grieved longer than 6 months (Newson et al, 2011;Saavedra Perez et al, 2015).…”
Section: Assessment Of Complicated Griefmentioning
confidence: 99%
See 2 more Smart Citations